2021
DOI: 10.1038/s41598-021-02748-4
|View full text |Cite
|
Sign up to set email alerts
|

Burial of microplastics in freshwater sediments facilitated by iron-organo flocs

Abstract: Microplastics are ubiquitous in standing freshwater bodies, consequently lakes and reservoirs may be important sinks for these contaminants. However, the mechanisms governing the deposition of microplastics and their interactions with the sediments are understudied. We demonstrate how aggregation-based transport facilitates the sinking and infiltration of buoyant microplastics into freshwater reservoir sediments by employing experiments with intact sediment cores. Buoyant polyethylene microplastics were rapidl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 71 publications
3
18
0
Order By: Relevance
“…The flocs sedimented to the bottom of the bottles and thereby mediated the sinking of the initially buoyant PE spheres. In a complementary study, it was shown that this mechanism is capable of aggregating and transporting approximately 99% of added PE microplastics into the sediments of Bautzen reservoir (Leiser et al 2021b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The flocs sedimented to the bottom of the bottles and thereby mediated the sinking of the initially buoyant PE spheres. In a complementary study, it was shown that this mechanism is capable of aggregating and transporting approximately 99% of added PE microplastics into the sediments of Bautzen reservoir (Leiser et al 2021b).…”
Section: Resultsmentioning
confidence: 99%
“…Once reaching the sediments, iron-organo flocs will experience anoxic conditions as long as the overlying water column remains stratified and anoxic. Given their high Fe oxide content (35-50%), iron-organo flocs are prone to iron reduction (Reiche et al 2011;Leiser et al 2021b), mediated by specialized sediment-dwelling bacteria such as freshwater Shewanella spp. and Geobacter spp.…”
mentioning
confidence: 99%
“…In fact, PE, which has a density < 1 g cm − 3 , was one of the most frequent polymer types found below 1950-level. Leiser, et al 49 have observed that aggregation to iron-organo ocs causes faster burial of PE particles and downward migration within sediment column up to 11 cm in unconsolidated muddy lake sediments 49 . Such mechanism can well have an important role.…”
Section: Drivers Of Microplastic Downward Migrationmentioning
confidence: 99%
“…In the eutrophic dimictic lakes with cycles of anoxic and oxic conditions at the bottom as a consequence of strati cation and mixing, favour oc formation. Leiser, et al 49 also suggested that the consequent gas formation within the anoxic sediment following the breaking of the ocs can have caused PE particles to sink further within the sediment column 44a . Although Leiser, et al 49 only tested PE particles, the mechanism can have importance in the burial of other plastic polymers as well.…”
Section: Drivers Of Microplastic Downward Migrationmentioning
confidence: 99%
“…Although there remains considerable controversy concerning the missing oceanic sink (Weiss et al, 2021), a large amount of plastics have been recovered from seafloor sediments (Kane et al, 2020), which infers the deep ocean is an ultimate sink for plastics (Woodall et al, 2014;Cózar et al, 2017). Freshwater sediment has also been considered as a transient or terminal sink for MPs (Leiser et al, 2021;Yang et al, 2021). Several hypotheses are proposed to explain the removal of MPs from surface waters (Michels et al, 2018;Foekema et al, 2013;Cole et al, 2016;Reisser et al, 2015;El Hadri et al, 2020), whereas the sinking of MPs caused by a density increase after biofouling (i.e., rapidly colonization of submerged MP surfaces by microorganisms) is considered to be an important pathway for the downward transport of MPs in the ocean and freshwaters (Fazey and Ryan, 2016;Kooi et al, 2017;Kaiser et al, 2017;Amaral-Zettler et al, 2021;Semcesen and Wells, 2021).…”
Section: Introductionmentioning
confidence: 99%